Circular Economy and Lean Production in Taiwan's Green Energy Industry: A Hybrid MADM-QFD Approach - Lai, Po-Yen (International Journal of Industrial Engineering: Theory, Applications and Practice, 2026)
The urgent need to implement and expand the Circular Economy (CE) has made it essential to develop an integrated evaluation model. Existing studies indicate that industries face numerous challenges in their transition to CE. This study conducts a series of quantitative analyses focusing on CE performance measurement, the relationship between Lean Production (LP) methods and CE, using Taiwan's green energy industry as the empirical research subject. The selection of this industry is based on its frontline role in sustainable development. The primary objectives of this study are to define critical CE performance indicators and investigate applicable LP methods. By applying the Quality Function Deployment method, particularly the House of Quality, this research analyzes the interaction between LP and CE, employing Multi-Attribute Decision-Making techniques to quantify LP’s contribution to CE performance. While prior research suggests that LP and CE can complement each other, their practical integration remains an area worth exploring. The results indicate that Visual Management emerged as the highest-impact LP method for enhancing CE performance, followed by Identification of Equipment Failure Points and Root Causes, Poka-Yoke, Production Management Kanban, and the Elimination of No-Load Operations. The findings of this study provide valuable insights for government agencies and corporate managers seeking to promote CE implementation.